Agitated Depression; The Challenges in Management and the Role of Maintenance Electroconvulsive Therapy - Janaki, V.; Suzaily, W. (IIUM Medical Journal Malaysia, 2019)
This case report highlights the challenges encountered and the role of maintenance electroconvulsive therapy (ECT) in the management of a depressed patient who presented with symptoms of agitation. Despite on an adequate dosage and duration of medications, the patient showed poor improvement and persistent agitation. Upon commencing maintenance ECT in addition to the pharmacotherapy, the patient’s condition markedly improved. As conclusion, maintenance ECT may be another option in managing agitated depression.